Effects of multiple injections on the combustion and hydrocarbon emission characteristics of the start cylinder in direct-start process. (15th July 2022) - Guo, Wenjun; Xiao, Maoyu; Zhang, Zhe; Wang, Yingyuan; Shi, Lei; Deng, Kangyao
Highlights: Multistage and split injection strategies are introduced into direct engine start. Effects of multistage injection number and split injection timing are investigated. Multistage and split injection strategies benefit combustion and HC emissions. Split injection timing of 1 ms best improves the engine's starting performance. Abstract: Improving the engine starting strategy is of great significance for enhancing its combustion and emission performances. Compared with conventional start-stop systems, the direct-start process has been widely considered an efficient, viable, and low-cost solution for gasoline direct injection (GDI) engines to guarantee frequent startups. This paper proposes a novel direct-start process by introducing multistage and split injection strategies to improve the fuel–air mixture preparation, in which the effects of injection numbers and split injection timings on combustion, motion, and hydrocarbon (HC) emission characteristics are experimentally investigated. Results show that both multistage and split injection strategies achieve better starting performances than the traditional single injection approach, with the significantly advanced start points of heat release and cylinder pressure, increased peak heat release rate (HRR), enhanced accumulative heat release, shortened CA50, and promoted start combustion efficiency. The faster and more complete combustion leads to a lower bottom point of the piston. Meanwhile, the HC emissions decrease, especially under equivalence ratios of 0.6–0.8. Comparing the two strategies, the direct-start process with a three-stage injection possesses an earlier start point of heat release, while that with a split injection timing of 1 ms holds a shorter CA50 (18.91 ms), higher peak HRR (∼200 J/ms), and higher start combustion efficiency (52.16%). Moreover, under the optimal equivalence ratio range of 0.6–0.8, the engine with the split injection timing of 1 ms has better motion and HC emission characteristics.